Estudio de teoría de colas en banco del austro del centro comercial “el condado” de la Ciudad de Quito - Veloz Guaranda, Esther Katherine (2022)
The present study was carried out at the Austro bank located in the “El Condado” shopping center in the Quito city, whose population objected to the study were users who came to said facilities during the on-site visits carried out in the present investigation. , the objective was to evaluate the efficiency of the service time in the window area, through the application of operations research when modeling studies of single-channel queues with Poisson arrivals and exponential service times and the model of multiple channels with Poisson arrivals and exponential service time for M / M / 2, M / M3 and M / M / 4, the purpose of which was an economic study of the waiting line generated at the facilities. The research had a descriptive non-experimental design, data collection techniques such as the survey, in situ observation and interviews were applied. Proposals for improvement and strategies were established to reduce the waiting time of customers, concluding that it is necessary to increase a third channel on monday, tuesday, wednesday and the dates of seasons where there is a greater flow of customers who attend the facilities, reducing the cost of the waiting line to $ 36.94, thus also establishing proposals related to the use of new technologies.